The legal concept of rural areas and the formation of this notion under the influence of European Union policy - Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2024)
The aim of this article is to define the legal meaning of the term "rural area" and to present the main concepts of this notion that function in law, taking into account the influence of EU policies, especially the Common Agricultural Policy, on their formation. The author analyses the different concepts of rural areas in law, and focuses on three main ones: the administrative, the functional and the comprehensive one. She concludes that it is difficult to define rural areas unambiguously and in a manner that would be universally accepted within the entire legal system. This is because there are various interpretations determined by the objectives of their delimitation and the specificity of legal regulations. The comprehensive concept of rural areas is considered to be the most broadly understood. Furthermore, the author notes that the changes in the conceptualisation of rural areas in law (including agricultural law) and in European Union policy reflect the directions of socio-economic and cultural changes taking place in the rural community.